2016
DOI: 10.1186/s40621-016-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of financial stressors and physical intimate partner violence perpetration

Abstract: BackgroundContextual factors, such as exposure to stressors, may be antecedents to IPV perpetration. These contextual factors may be amenable to modification through intervention and prevention. However, few studies have examined specific contextual factors. To begin to address this gap, we examined the associations between financial stressors and three types of physical IPV perpetration.MethodsThis analysis used data from Wave IV of The National Longitudinal Study of Adolescent to Adult Health. We used logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 51 publications
5
67
0
Order By: Relevance
“…Our results suggest that perceived economic difficulties in the household increase the probability of current physical/sexual IPV. There is evidence that financial stressors in the home increase the probability of exposure to within-family violence24; this is a variable that longitudinal studies have identified as a clear predictor of lifetime IPV 25…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that perceived economic difficulties in the household increase the probability of current physical/sexual IPV. There is evidence that financial stressors in the home increase the probability of exposure to within-family violence24; this is a variable that longitudinal studies have identified as a clear predictor of lifetime IPV 25…”
Section: Discussionmentioning
confidence: 99%
“…In Baltimore, for example, female adolescents who were raised by other relatives were actually less likely to be sexually experienced compared to those raised by two biological parents. Although we did not ask adolescents about the quality of their parents’ relationship, there have been studies that have shown that couples and families who face economic hardships also experience higher levels of relationship conflict–which has also been shown to be related to female adolescents’ sexual experiences [2022]. In addition, as shown by the quotes shared by adolescents from Baltimore, many parents, even if physically present, were not available, and many adolescents described the prevalence of drug and alcohol use and violence in their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Nationwide stay-at-home policies following the COVID-19 pandemic abruptly interrupted daily life and introduced strains or exacerbated stressors (like job loss, poor mental health and lack of social support) across the USA. 1 2 Past literature has shown parenting stress, 3 economic hardship, 4 food insecurity, 5 eviction threat and utilities nonpayment 5 increase the risk of violence, like intimate partner violence (IPV). The Centers for Disease Control and Prevention (CDC) define IPV as abuse or aggression that occurs in a close relationship of current or former spouses and dating partners.…”
Section: Introductionmentioning
confidence: 99%